PERIODISMO TELEVISIVO Y SU INFLUENCIA EN EL DESARROLLO CULTURAL DEL CANTÓN PALENQUE. - Moran carriel, Karla Thalia (2022)
The main objective of this research study is to analyze the quality and increase the frequency of local television content in order to strengthen culture in the Palenque canton; In the development of this investigative work, field and bibliographical research were used to make this study less complex. For the collection of information, the survey was applied to a sample of 144 inhabitants of the canton. The results obtained in this investigation made it possible to make visible that television journalism has a great influence on the cultural development of the inhabitants of the Palenque Canton; Therefore, it is suggested to make an observation to those who carry out television journalism in the local media and broadcast more frequently programs that contribute to the preservation and cultural development of the inhabitants of the Canton.